Does The Losses Due To Disaster Have Any Contribution on Economic Growth? - Rizka Zulfikar; Farida Yulianti; Purboyo Purboyo; Kumara Efrianti (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
This study aims to measure the impact of losses on economic development in South Kalimantan Province. This study's economic development indicators include the Human Development Index (HDI), Economic Growth, and Gini Ratio. In comparison, the indicators of the impact of environmental damage are the number of disasters, the number of losses, and the number of people affected. The data used is secondary data for the period 2009-2021 sourced from DLH, BNPB South Kalimantan. The method used in this research is descriptive quantitative and SEM. The findings obtained from this study are 1) The Number of disasters has no significant effect on losses because of the value of CR (1.888) < 1.96 and probability (0.059) > 0.05. 2) The amount of loss has no significant effect on the number of affected people because of the value of CR (0.774) < 1.96 and probability (0.439) > 0.05. 3) The amount of loss has a significant effect on HDI because of the value of CR (3.358) 1.96 and probability (0.000) < 0.05. 4) The amount of loss has no significant effect on the Gini Ratio because the value of CR (0.087) < 1.96 and probability (0.931) > 0.05, 5) The amount of loss has a significant effect on Economic Development. After all, the value of CR (2.354) 1.96 and probability (0.019) < 0.05, 6) Contribution figures are only indicated by the level of losses to Economic Growth (13.38%) and HDI (24.12%). At the same time, other disaster indicators analyzed do not show any contribution to the components of economic growth.